Creativity: How to Develop an Entrepreneurial Attitude of Creativity - Prety Diawati; Abu Muna Almaududi Ausat; Jeneva Augustin (Journal on Education, 2023)
Entrepreneurs must have an independent spirit. But that is not enough, entrepreneurs must be equipped with an attitude of high creativity so that the business they build has the potential to become great. This research aims to provide information related to various ways to develop entrepreneurial creativity. This research includes library research, because the research was conducted to search, analyze, make interpretations and generalizations from the facts of the results of thoughts and ideas written by experts in entrepreneurship and entrepreneurship. This research is descriptive qualitative with a secondary data analysis approach. The results of this study explain that there are various important ways that entrepreneurs can implement in order to create an attitude of creativity, one of which is by enriching literacy. Someone who is equipped with extensive knowledge is sure to have high creativity. The results of this study are expected to be a source of reference for anyone with an interest in aspects of entrepreneurship and creativity.